PENYULUHAN PENDIDIKAN DIGITAL KELUARGA SEBAGAI UPAYA MENERAPKAN KEAMANAN DIGITAL KELUARGA DI PKBM TINTA ILMU TANGERANG SELATAN - Puspitasari, Tita (Fakultas Teknologi Informasi dan Industri Unisbank, 2025)
The Digital Education Counseling for Families held at the Tinta Ilmu Community Learning Center (PKBM) in South Tangerang is an effort to implement digital security for parents and schools to support students’ learning in the digital era. Digital education has become a necessity and an innovative way to align educational traditions with technological developments. The development of digital technology has a significant impact on children’a lives. Esay access to digital devices has the potential to cause various problems, therefore, good guidance and communication between students, schools, and prents are essential. The lack of outreach provided by schools and the lack of initiative from parents to independently seek information regarding current digital education developments are weaknesses that must be addressed immediately to mitigate the negative impacts of the current digitaleducation system. This counseling is expected tohelp parents and teachers collaborate in monitoring learning activities involving the digital world, ensuring protection from unnecessary and potentially harmful content. This is expected to create a safer and more conducive digital education for students.